Annual report of the Committee on Gynecologic Oncology, the Japan Society of Obstetrics and Gynecology: Annual Patient Report for 2018 and Annual Treatment Report for 2013. Issue 3 (13th January 2022) - Nagase, Satoru; Ohta, Tsuyoshi; Takahashi, Fumiaki; Yamagami, Wataru; Yaegashi, Nobuo; ,
Abstract: To provide information including the trend of gynecological malignancies in Japan, we hereby present the Annual Patient Report for 2018 and the Annual Treatment Report for 2013, on the outcomes of patients who started treatment in 2013. The Japan Society of Obstetrics and Gynecology maintains an annual tumor registry, where information on gynecological malignancies from various participating institutions is gathered. The data of patients whose treatment with gynecologic malignancies was initiated in 2018 were analyzed retrospectively. Survival of the patients who started treatment with cervical, endometrial, and ovarian cancer in 2013 was analyzed by using the Kaplan–Meier, log‐rank, and Wilcoxson tests. Treatment was initiated in 2018 for 7304 patients with cervical cancer; 11 230 with endometrial cancer; 7031 with ovarian, tubal, and peritoneal cancer; 2072 with ovarian borderline tumors; and with the others (222 vulvar cancer, 159 vaginal cancer, 413 uterine sarcoma, 54 uterine adenosarcoma, and 135 trophoblastic diseases). This clinicopathological information was summarized as the Patient Annual Report. The 5‐year survival rates of the patients with cervical cancer were 93.1%, 75.9%, 59.1%, and 31.2% for Stages I, II, III, and IV, respectively. The 5‐year survival rates for the patients with endometrial cancer were 94.1%, 89.2%, 73.6%, and 25.8% for Stages I, II, III, and IV, respectively. The 5‐year survival rates for the patients with ovarian cancer (surface epithelial‐stromal tumors) were 89.7%, 76.8%, 49.1%, and 32.4% for Stages I, II, III, and IV, respectively. The annual report is important to provide knowledge on gynecological malignancy trends in Japan.